FACTORS AFFECTING ENTREPRENEURIAL INTENTION FOR THE STUDENTS OF BUSINESS AND ECONOMICS FACULTY IN UNIVERSITAS SURABAYA - Tifani Geovana Suyono; Joseph L. Eko Nugroho; Noviaty Kresna Darmaetiawan (Manajemen dan Bisnis, 2017)
This study aimed to examine the factors affecting entrepreneurial intention of students such as education factor, relationship factor and self-confidence factor from students of Faculty of Business and Economics, University of Surabaya.This study used a quantitative approach by distributing questionnaires to 150 respondents. The software used to analyze the data was SPSS 18 for Windows and IBM Amos 22 for Windows. The samples in this research were the students of Faculty Business and Economics of University of Surabaya. The Dependent Variable in this research was entrepreneurial intention. The Independent variables in this study consisted of education support, relationship support and self-confidence. The study found that education support had a positive significant effect on entrepreneurial intention on the students of Faculty of Business and Economics University of Surabaya. Relationship support had a positive significant effect on entrepreneurial intention from students of Faculty of Business and Economics University of Surabaya. Self-confidence had a positive significant effect on entrepreneurial intention from students of Faculty of Business and Economics University of Surabaya.